Mapping the literature of occupational therapy: an update - Potter, Jonathan (Medical Library Association, 2010)
OBJECTIVES: This study updated Reed's 1999 “Mapping the Literature of Occupational Therapy.” An analysis of citation patterns and indexing coverage was undertaken to identify the core literature of occupational therapy and to determine access to that literature. METHODS: Citations from three source journals for the years 2006 through 2008 were studied following the common methodology of the “Mapping the Literature of Allied Health Project.” Bradford's Law of Scattering was applied to analyze the productivity of cited journals. A comparative analysis of indexing was conducted across three bibliographic databases. RESULTS: A total of 364 articles cited 10,425 references. Journals were the most frequently cited format, accounting for 65.3% of the references, an increase of 4.1% over the 1999 study. Approximately one-third of the journal references cited a cluster of 9 journals, with the American Journal of Occupational Therapy dominating the field. An additional 120 journals were identified as moderately important based on times cited. CINAHL provided the most comprehensive indexing of core journals, while MEDLINE provided the best overall coverage. CONCLUSIONS: Occupational therapy is a multidisciplinary field with a strong core identity and an increasingly diverse literature. Indexing has improved overall since 1999, but gaps in the coverage are still evident.